Sympathetic Ophthalmitis - Mohammad Ali Ayaz Sadiq, Tanvir Abbas, Asad Aslam Khan (Pakistan Journal of Ophthalmology, 2015)
Sympathetic ophthalmitis is a rare bilateral granulomatous panuveitisoccurring after ocular penetrating trauma most frequently associated with uveal tissue prolapse. It can also occur following ocular surgery like cataract, vitrectomy, trabeculectomy, retinal detachment surgery and even after laser photocoagulation. Incidence varies between 0.05% to 0.2% following penetrating trauma and 0.01% following ocular surgery. Key words: Sympathetic Ophthalmitis, Granulomatous panuveitis.